Social and Economic Benefits of CIFOR’s Sustainable Wetlands Adaptation and Mitigation Program (SWAMP) - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2018)
The Sustainable Wetlands Adaptation and Mitigation Program (SWAMP) (https://www.cifor.org/swamp) of the Center for International Forestry Research (CIFOR) (https://www.cifor.org/) aims to provide policy makers with the scientific information they need to make sound policy and strategy decisions about wetlands. Researchers from Virginia Tech (https://aaec.vt.edu/research/rural-regional-development/spia.html) and CIFOR estimated the potential economic value of SWAMP-generated knowledge through two pathways: (1) improved implementation of the Indonesian forest moratorium in peatlands, and (2) increased retention of peatlands and mangroves worldwide.